Orthognathic Surgery P-54277989-337 Comparative study between three techniques for alar cinch sutures on bimaxilar orthognathic surgery. Double-blind randomized clinical trial. (February 2023) - Costa, S.; Ribeiro, B. Campos; De Toledo, G. Lacerda; Amaral, M. Figueiredo
Abstract : Purpose: To compare three techniques for alar cinch sutures for nasal width maintenance on bimaxilar orthognathic surgery. Methods: A double-blind randomized clinical trial was proposed in order to compare the conventional alar cinch suture with the hybrid, that is anchored on the subcutaneous tissue and the one that is anchored on the synthesis material. All the patients were enrolled with the indication for bimaxillary orthognathic surgery. The alar base was measured at the pre-op, and at immediate post-operative time, 30, 60, 90, 120 and 180 days of postoperative time. Comparative statistical analysis were performed in order to address the better choice for the control of the nasal base musculature. Results: A total of 24 patients were enrolled and subdivided in their groups. The hybrid technique presented better control of the alar base region, p=0, 037. In addition to that, the others techniques did not were effective in the prevention of the nasal enlargement, with an average increase of at least 2 mm wide. Conclusions: To date, there still no agreement on the gold-standard technique for the management of the muscles around the piriform aperture on orthognathic surgery. This study suggest that the hybrid one, anchored on the subcutaneous tissue present the better results, avoiding the nasal width enlargement. On the other hand, there are still need for more studies, specially those comparing the hybrid alar cinch suture with the subspinal osteotomy.